Bookkeeping techniques in historical perspective - Banaszkiewicz, Aleksandra (Copernican Journal of Finance & Accounting, 2013)
Accounting history researchers agree on the fact that a double accounting system is not an invention of one man, or by chance. This is probably the result of tests and experiments carried out by a number of merchants and bankers in various Italian cities. Over the years, the accounting system was improved. The oldest technique is the method of Italian bookkeeping, otherwise known as Venetian accounting. By the end of the eighteenth century as part of a double accounting was created a few ways to make entries in the books trade. The most commonly used is the method: Italian, French and German. Nineteenth and early twentieth century brought new accounting methods, such as the American method.